2007
DOI: 10.1093/humrep/dem247
|View full text |Cite
|
Sign up to set email alerts
|

Dual repressive effect of angiotensin II-type 1 receptor blocker telmisartan on angiotensin II-induced and estradiol-induced uterine leiomyoma cell proliferation

Abstract: BACKGROUND: Although uterine leiomyomas or fibroids are the most common gynecological benign tumor and greatly affect reproductive health and well-being, the pathophysiology and epidemiology of uterine leiomyomas are poorly understood. Elevated blood pressure has an independent, positive association with risk for clinically detected uterine leiomyoma. Angiotensin II (Ang II) is a key biological peptide in the renin-angiotensin system that regulates blood pressure. METHODS: In this study, we investigated the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 28 publications
0
29
0
Order By: Relevance
“…Angiotensin II is an important blood pressure control pathway that has been linked to growth and proliferation of uterine leiomyoma. Studies utilizing the Eker rat model indicate that ANGII induced ELT3 cell proliferation via upregulation of the AT1R 11,29 and that proliferation was inhibited by AT1R blockade. 11 In the current study, in vitro blockade of the AT1R with Losartan decreased ET-1 secretion in uterine fibroids which supports a role for the renin-angiotensin system in ET-1 secretion from uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II is an important blood pressure control pathway that has been linked to growth and proliferation of uterine leiomyoma. Studies utilizing the Eker rat model indicate that ANGII induced ELT3 cell proliferation via upregulation of the AT1R 11,29 and that proliferation was inhibited by AT1R blockade. 11 In the current study, in vitro blockade of the AT1R with Losartan decreased ET-1 secretion in uterine fibroids which supports a role for the renin-angiotensin system in ET-1 secretion from uterine fibroids.…”
Section: Discussionmentioning
confidence: 99%
“…AngII was used at concentrations of 1, 10, 100 or 1000 nM (9). An active compound, telmisartan, which is a novel, long-acting, selective AT-1 receptor antagonist, was purchased from Sigma-Aldrich (St. Louis, MO, USA) and used at concentrations of 100 and 1000 nM, according to a previous report (24). Transforming growth factor (TGF)-ß1 was purchased from Sigma-Aldrich and was used at a concentration of 10 ng/ml, according to a previous report (25).…”
Section: Methodsmentioning
confidence: 99%
“…Ang II-induced proliferation of leiomyoma cells has been shown [26]. Experimental findings in vitro also highlight the potential role of Ang II in the proliferation of leiomyoma cells [27].…”
Section: Introductionmentioning
confidence: 85%
“…In 2007, Isobe et al [26] investigated the role of Ang II in the proliferation of rat ELT-3 leiomyoma cells (Eker rat uterine leiomyoma-derived smooth muscle cells) in vitro. They found that Ang II significantly induced ELT-3 leiomyoma cell proliferation and the expression of AT1R and AT2R mRNA and protein was confirmed.…”
Section: Discussionmentioning
confidence: 99%